Palaeohydrological reconstruction of Siwalik Group in Surai Khola - Ulak, Prakash Das (Journal of Nepal Geological Society, 2006)
About 5 km thick Neogene Siwalik Group in the Surai Khola section of west Nepal comprises many fining-upward cycles, which are from several metres to tens of metres thick. However, the Siwalik sequence as a whole reveals a coarseningupward trend. The palaeohydrological reconstruction of the Siwalik Group was based mainly on two parameters: the sediment grain size and the thickness of individual fining-upward successions. The estimated palaeoflow velocity in the Siwalik Group varies from 0.32 to 4.76 m/s, palaeochannel gradient ranges from 5.29x10-5 to 9.59x10-4 m/m, and palaeodischarge fluctuates from 1 to 104 m3/s, in the stratigraphically upward direction. These palaeohydrological parameters indicate a gradual change in fluvial system, presumably owing to the southward propagation of thrusts.